Model Manajemen Sumber Daya Manusia Dan Mutu Lulusan di Dayah Modern Yapena Lhokseumawe - Linawati, Linawati; Mannan, Mannan (Adaara: Jurnal Manajemen Pendidikan Islam, 2024)
ABSTRACTThis study aims to identify the stages of the Human Resources Management Model (HRM) at Dayah Modern Yapena Lhokseumawe, including 1) Recruitment Management, 2) Placement Management, 3) Development Management, and 4) The Effect of HR Management on Graduate Quality. The research used descriptive qualitative methods with data collection techniques through observation, interviews, and documentation. The results showed that the recruitment process includes mapping skills needs, closed announcements, oral and written test selection, and work orientation. Placement of educators according to qualifications, and various development programs have been carried out, such as language training and fiqh programs. Internal evaluations are conducted twice a year and externally four times a year, despite workload and budget constraints. The quality of graduates has proven to be very good with many alumni being accepted into reputable universities and student achievements in various competitions.Â